Effects of Feeding Kroto (Aerophylla smaragdina), Kricket (Brachytrypes membranaceus) and Diet Combinations on Live Performance of Young Edible –Nest Swiftlet (Collocalia fuciphaga) - B. Brata; R. Saepudin; Sutriyono Sutriyono; Lindya Lindya (Jurnal Sain Peternakan Indonesia, 2011)
ABSTRACTThe aim of this research was to investigate the performance of young Edible-nest Swiftlet (Collocalia fuciphaga) fed (Aerophylla smaragdina), cricket (Brachytrypes membranaceus) and diet combinations of 33% cricket, 34% kroto and 33% of commercial diet/BR1. The observation was started from the bird hatches until it fledges. Experiment design used was completely randomized design with three treatments and four replications; each of the replications consists of ten young Edible-nest Swiftlet (Collocalia fuciphaga). The treatments were 100% kroto, 100% cricket and diet combinations of of 33% cricket (Brachytrypes membranaceus), 34% kroto and 33% of commercial diet/BR1. The variables measured were feed consumption, body weight, feed conversion and total loss. Results showed that, there were insignificant effects of feeding kroto, cricket and diet combinations of 33% cricket, 34% kroto and 33% of commercial diet/BR1 on live performance of young Edible-nest Swiftlet, observed from the bird hatches until it fledges. By the end of the observation, one young Edible-nest Swiftlet (Collocalia fuciphaga) survived.Keywords: young edible-nest swiftlet (Collocalia fuciphaga) , kroto and cricket.